Constructing biomimetic liver models through biomaterials and vasculature engineering. (12th October 2022) - Lv, Weikang; Zhou, Hongzhao; Aazmi, Abdellah; Yu, Mengfei; Xu, Xiaobin; Yang, Huayong; Huang, Yan Yan Shery; Ma, Liang
Abstract: The occurrence of various liver diseases can lead to organ failure of the liver, which is one of the leading causes of mortality worldwide. Liver tissue engineering see the potential for replacing liver transplantation and drug toxicity studies facing donor shortages. The basic elements in liver tissue engineering are cells and biomaterials. Both mature hepatocytes and differentiated stem cells can be used as the main source of cells to construct spheroids and organoids, achieving improved cell function. To mimic the extracellular matrix (ECM) environment, biomaterials need to be biocompatible and bioactive, which also help support cell proliferation and differentiation and allow ECM deposition and vascularized structures formation. In addition, advanced manufacturing approaches are required to construct the extracellular microenvironment, and it has been proved that the structured three-dimensional culture system can help to improve the activity of hepatocytes and the characterization of specific proteins. In summary, we review biomaterials for liver tissue engineering, including natural hydrogels and synthetic polymers, and advanced processing techniques for building vascularized microenvironments, including bioassembly, bioprinting and microfluidic methods. We then summarize the application fields including transplant and regeneration, disease models and drug cytotoxicity analysis. In the end, we put the challenges and prospects of vascularized liver tissue engineering. Graphical Abstract: